2000
DOI: 10.1002/1098-1004(200010)16:4<315::aid-humu4>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

High mutation detection rate in TCOF1 among Treacher Collins syndrome patients reveals clustering of mutations and 16 novel pathogenic changes

Abstract: Twenty-eight families with a clinical diagnosis of Treacher Collins syndrome were screened for mutations in the 25 coding exons of TCOF1 and their adjacent splice junctions through SSCP and direct sequencing. Pathogenic mutations were detected in 26 patients, yielding the highest detection rate reported so far for this disease (93%) and bringing the number of known disease-causing mutations from 35 to 51. This is the first report to describe clustering of pathogenic mutations. Thirteen novel polymorphic altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
3
14

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(104 citation statements)
references
References 7 publications
(7 reference statements)
3
84
3
14
Order By: Relevance
“…We observed in each situation that 20 and 28% of patients needed feeding or respiratory support, respectively, compared with 11% who needed respiratory support in the study by Teber et al 2 ( Table 1). Cleft palate was less frequent in our study (22%) compared with those by Teber et al 2 (33%) and Splendore et al 18 (28%) ( Table 1). Surprisingly, we observed a high rate of congenital cardiac defects in patients with mutations in TCOF1 (8%), which was never described in the literature.…”
Section: Clinical Datacontrasting
confidence: 56%
See 4 more Smart Citations
“…We observed in each situation that 20 and 28% of patients needed feeding or respiratory support, respectively, compared with 11% who needed respiratory support in the study by Teber et al 2 ( Table 1). Cleft palate was less frequent in our study (22%) compared with those by Teber et al 2 (33%) and Splendore et al 18 (28%) ( Table 1). Surprisingly, we observed a high rate of congenital cardiac defects in patients with mutations in TCOF1 (8%), which was never described in the literature.…”
Section: Clinical Datacontrasting
confidence: 56%
“…In this study we identified 47 novel mutations spread throughout the TCOF1 gene and only one clustering located in exons 23 and 24, which contained 27% of the mutations. The common 5-bp deletion in exon 24 (p.Lys1457Glufs) was present in 7% of patients in our series compared with 20% of patients in the study by Splendore et al 18 and none in the study by Teber et al 2 We hypothesize that the distinct geographic origin of the patients between studies explains such difference (Brazilian versus European centers), given that population in our study was quite diverse.…”
Section: Molecular Datacontrasting
confidence: 45%
See 3 more Smart Citations